The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fmicb.2022.886161
|View full text |Cite
|
Sign up to set email alerts
|

Linking Microbial Community Succession With Substance Transformation in a Thermophilic Ectopic Fermentation System

Abstract: Ectopic fermentation system (EFS) is an effective technology for treating mass livestock manure. However, the associations between microbial communities and substance transformation remain controversial. This study aimed to investigate chicken manure EFS lasting 170 days using 16S rRNA sequencing and electrochemical, spectroscopic, and chromatographic analyses. The results showed a noticeable transformation of protein-like substances into humus-like substances. Meanwhile, the electron–accepting capacity increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Electrochemical strategies have been extensively reported to enrich electroactive microorganisms in anaerobic aggregations to accelerate the bio-oxidation of organics in the anode or CO 2 reduction in the cathode, , which might promote methane production in the anaerobic digestion of waste-activated sludge (WAS), food waste, livestock manure, and so forth. Notably, the electrical treatment also decreased the internal resistance of anaerobic aggregations, which benefited the electron exchange of the enriched electroactive microorganisms. Yu and Zhang reported that protein-like substances were polarized to increase the conductivity and capacitance of the anaerobic aggregations during the long-term electro-stimulation .…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical strategies have been extensively reported to enrich electroactive microorganisms in anaerobic aggregations to accelerate the bio-oxidation of organics in the anode or CO 2 reduction in the cathode, , which might promote methane production in the anaerobic digestion of waste-activated sludge (WAS), food waste, livestock manure, and so forth. Notably, the electrical treatment also decreased the internal resistance of anaerobic aggregations, which benefited the electron exchange of the enriched electroactive microorganisms. Yu and Zhang reported that protein-like substances were polarized to increase the conductivity and capacitance of the anaerobic aggregations during the long-term electro-stimulation .…”
Section: Introductionmentioning
confidence: 99%
“…The EFS is a bulking material-padded experimental apparatus, which is dynamically fermented by inoculation with a composite microbial agent and continual addition of animal wastes [ 11 ]. With the features in large-scale disposal of organic solid wastes, EFS has attracted growing attention from applied researchers and engineers as an ex situ decomposition technique [ 10 ]. EFS was a unique and ecologically acceptable way of treating both excrement and urine, and the discharged waste and post-fermentation padding may be utilized as bio-fertilizers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ectopic fermentation system (EFS), composed of complex microbial communities mixed with litter, was developed to overcome the problem of pollution from existing farm wastewater systems [7]. It had been evidenced by several studies in effectively managing pollution problems related to livestock wastes such as cow, pig, and so on [4,[8][9][10]. The EFS is a bulking material-padded experimental apparatus, which is dynamically fermented by inoculation with a composite microbial agent and continual addition of animal wastes [11].…”
Section: Introductionmentioning
confidence: 99%